Formal aspects of component software : 16th International Conference, FACS 2019, Amsterdam, the Netherlands, October 23-25, 2019, Proceedings /: 16th International Conference, FACS 2019, Amsterdam, the Netherlands, October 23-25, 2019, Proceedings. (2020) - Unknown
No abstract available